Christology and Anti-Heretical Strategies in the In Iohannis euangelium tractatus - Drecoll, Volker Henning (Augustinian studies, 2017)
Scholars agree that Christology is at the center of the In Iohannis euangelium tractatus. In his exegesis of the Gospel of John, Augustine particularly highlights the human nature of the Incarnated, even as he integrates Trinitarian arguments (which he had developed earlier in his De trinitate) as a cornerstone of his homiletic teaching. This may have been important for the later reception of Augustine’s Trinitarian thought. Christology is clearly present throughout the various parts of the work. The differences between the parts can be traced to the various contexts in which they were composed and/or delivered: e.g., the Anti-Donatist controversy that is behind the first sermons, and the Anti-Pelagian and Anti-Homean controversies that often fueled the later ones. Sometimes anti-heretical strategies are used as a crucial step for advancing the teaching of the preacher (not least because they can directly promote knowledge of the fundamentals of the faith), even if the heresy being opposed is of no immediate relevance or importance to the North Africa of Augustine’s day (e.g., that of the "Sabellians" or the "Apollinarians"). Surprisingly, the second half of the work (consisting as it does of shorter homilies or, better, drafts of homilies) contains various passages in which anti-heretical strategies were clearly pursued. It is particularly Augustine’s Anti-Pelagian strategy that provides us with clues regarding the historical context of this part of the work.